The fluctuations of Zn impurity Concentration Profile in KCl crystals growth by various pulling rate Czochralski method - Heidar Faripour; Elham Khodadoost; Yasaman Faripour (Progress in Physics of Applied Materials, 2023)
Single crystals of KCl(Zn) using different amounts of Zn impurity (0.5 and 1.0 mole percents) with and without rotating crucible were grown by Czochralski method. The speed of rotation and pulling rate of the seed crystal were adjusted at, 10 rpm and 12 mm per hour respectively. The crucible was rotated, in the opposite direction of crystal rotation, with 5 rpm. Crystals, with Zn impurity of 0.5 % grown by both rotating and fixed crucible, were found to be transparent and uniform. Since the KCl crystals with Zn impurity of 1% were not transparent, they were found not suitable for optics. Furthermore, it was observed that the upper and middle parts of the crystals grown with 1 mol% Zn impurity are more transplant but the lower part includes transplant and cloudy layers. The results show that a convenient rotation and pulling rate can improve the stability and uniformity of impurity distribution along the crystals.